A prospective study of BISAP score in assessing severity of acute pancreatitis - Venkatapuram, Mahidhar Reddy; Sateesh, Sreeram; Batchu, Deepthi (International Surgery Journal, 2018)
Background: Aim of study is to prospectively evaluate the ability of the Bedside Index for Severity in Acute Pancreatitis (BISAP) score to predict mortality as well as intermediate markers of severity. Methods: 50 patients admitted from December 2015 to November 2017 with acute pancreatitis were included in the study. BISAP score is calculated in all such patients based on data obtained within 24hrs of hospitalization. Patients were assessed for organ failure according to Marshall scoring system and followed throughout hospitalization for assessment of complications. Statistical analyses were made using Fischer’s exact probability test. The difference was assumed statistically significant when p<0.05. Results: There was a statistically highly significant trend for increasing mortality (p < 0.05) and intermediate markers of severity (p<0.05) that is transient organ failure, persistent organ failure and pancreatic necrosis with BISAP score ≥3. Conclusions: The BISAP score represents a simple way to identify patients at risk of increased mortality and the development of intermediate markers of severity within 24 hours of presentation.